The competitive advantage of Malaysian SME's: the impact of uncertainity avoidance - A missing element in Porter's analysis - Hussain, Fawad; Nik Abdullah, Nik Ab. Halim; Hassan, Mohamad Ghozali
This article is based on criticizing Michael Porter's model of national 'diamond' to explore the role of Malaysian uncertainty avoidance factor in the competitive position of SMEs andfirms.It is believed; however, that the influence of uncertainty avoidance on the competitive advantage of SME S or firms is too weakly elaborated in Porter's Diamond.In particular, the Porter's Diamond has neglected to discuss strong or weak uncertainty avoidance behavior among the firm's or SME's.This paper is looking Porter's Diamond weakness in term of Malaysian SMES uncertainty avoidance factor.